The provenance of stress among employee in Hospital Sultanah Aminah, Johor Bahru / Nurul Azwa Ezzuren Zulkifli - Zulkifli, Nurul Azwa Ezzuren (Faculty of Business and Management, 2018)
This study aims to explore the reasons for stress among representatives in government hospitals which is in Sultanah Aminah Hospital, Johor Bahru. Work assumes a focal part in the lives of many individuals and hence the effect of work related anxiety is a vital issue both for singular representatives and the associations in which they work. Stress experienced at work can have adverse results for the prosperity of individual employees and association as entirety. The present study plans to research the reasons for stress among representatives in government healing facilities which is Sultanah Aminah Hospital, Johor Bahru. Hospital work stress is a nosocomial anxiety described by stressors like work over-burden, under staffing, utilization of repetitive hardware, poor advancement, poor administrative association with staff, poor workplace, unnecessary or delayed working hours and numerous others. This investigation sought to decide the provenance of work stress among medicinal services labourers in Sultanah Aminah Hospital, Johor Bahru. Information was gathered using primary and secondary source. 150 surveys were managed through convenient sampling. The findings of this study will be measured using Statistical Package for the Social Science (SPSS) with descriptive analysis, reliability analysis, pearson correlation analysis and multiple regression. The objective of this study is to measures the relationship between job enrichment, facilities and job satisfaction with provenance of stress among workers in Sultanah Aminah Hospital, Johor Bahru.